Cover Feature: Charge Transfer Reactions in CO2 Electroreduction on Manganese Doped Ceria (ChemElectroChem 6/2019). Issue 6 (27th February 2019) - Huang, Zhidong; Shang, Lei; Qi, Huiying; Zhao, Zhe; Tu, Baofeng; Yang, Weishen; Cheng, Mojie
Abstract : The Cover Feature presents the charge‐transfer reactions for carbon dioxide electroreduction on manganese‐doped ceria (CMO) in a solid oxide electrolysis cell. The electroreduction of CO2 to CO on CMO passes through two elementary charge‐transfer reactions. The later one is the key rate‐determining step. More information can be found in the Communication by Z. Huang et al. on page 1668 in Issue 6, 2019 (DOI: 10.1002/celc.201801427 ).